2000
DOI: 10.1007/s004170000154
|View full text |Cite
|
Sign up to set email alerts
|

Visual and anatomical success with short-term macular tamponade and autologous platelet concentrate

Abstract: The combination of SF6 gas, platelet concentrate, and short-term prone posturing gave a degree of anatomical and visual success comparable to that of the group which had longer tamponade. Although no differences were statistically significant, several trends did emerge; in group 2, patients recovered visual acuity faster, had fewer IOP spikes, and there were fewer cases of PSCC formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…Two comparative studies in the 1990s showed that the use of long-acting C 3 F 8 gas and prolonged prone positioning (for more than 2 weeks) provided a better improvement in visual acuity and a higher rate of MH closure [12,13]. However, later trials found that a short tamponade by short-acting gases and shorter face-down posturing (for up to 10 days) provided anatomical and visual outcomes comparable to those associated with a longer tamponade [5,14,15,16]. Moreover, two recent multicentre randomised controlled trials (RCTs) suggested that no face-down posturing was necessary for small MHs (<400 μm) [15,16].…”
Section: Mh Surgerymentioning
confidence: 99%
“…Two comparative studies in the 1990s showed that the use of long-acting C 3 F 8 gas and prolonged prone positioning (for more than 2 weeks) provided a better improvement in visual acuity and a higher rate of MH closure [12,13]. However, later trials found that a short tamponade by short-acting gases and shorter face-down posturing (for up to 10 days) provided anatomical and visual outcomes comparable to those associated with a longer tamponade [5,14,15,16]. Moreover, two recent multicentre randomised controlled trials (RCTs) suggested that no face-down posturing was necessary for small MHs (<400 μm) [15,16].…”
Section: Mh Surgerymentioning
confidence: 99%
“…4 However, the value of face-down positioning following surgery is unproven. Results of a number of studies question the value of posturing, demonstrating favourable outcomes with shortened durations of posturing, [5][6][7] and with no posturing at all. [8][9][10] Furthermore, face-down positioning is an arduous challenge and the prospect can be a significant deterrent to surgery for some people.…”
Section: Introductionmentioning
confidence: 99%
“…These platelet preparations have been applied in diverse clinical fields. They have been used locally by ophthalmologists as an adjuvant to the ophthalmologic treatment of macular holes [10,11]; they have been used in cases of bone grafting showing to promote bone formation [12,13]; and they have proved effective in healing of chronic venous ulcers in cases of vascular surgery and dermatology [14,15]. Platelet concentrates has also been found to enhance healing of various kinds of wounds [16,17].…”
Section: Discussionmentioning
confidence: 99%